Development of Logistics Processes in Aviatıon Maintenance and Repair Center: Case of Turkish Technic - Eraslan, Mehmet; Sezen, Bülent (Aksaray University, 2023)
Maintenance, Repair and Overhaul (MRO) services of aircraft components are an important process in the aviation industry, but they constitute a large part of the costs. It is important to be a preferable MRO in order to get a share of the cake and strengthen position in the sector with the fact that an aircraft has a life span of more than 25-30 years and has a durable structure and prediction that component maintenance services will replace heavy maintenance revenues in the following years. To achieve this, TAT (Turn Around Time) and reasonable price offer are the biggest factors in the main decision orientation of the customers. This research will focus on logistics applications and gains from improvements in these processes to support MRO service in aviation. In the aviation industry, the concept of MRO and the general processes of MRO services will be defined as the main element of the service sector. The effect of logistics on MRO will be examined and modeled on the relevant units and in this scope, how much time and job losses occur in which areas will be determined by Pareto and Root-Cause analyses. According to the results of the analysis, the necessary improvement studies will be implemented more effectively by focusing on important areas.

Havacılık endüstrisinde uçak komponentlerinin Bakım (Maintenance), Onarım (Repair) ve Revizyon (Overhaul) (MRO) hizmetleri önemli bir süreç olmakla birlikte maliyetlerin büyük bir kısmını oluşturmaktadır. Bir uçağın ortalama 25-30 yıldan fazla ömre sahip dayanıklı bir yapıda olduğu gerçeği ve ilerleyen yıllarda ağır bakım gelirlerinin yerini komponent bakım hizmetlerinin alacağı öngörüsü ile bu büyük pastadan pay alabilmek ve sektördeki konumunu güçlendirmek için tercih edilebilir bir MRO olmak önemlidir. Bunu sağlamak için de TAT (Turn Around Time) ve uygun fiyat teklifi müşterilerin ana karar yöneliminde en büyük etkendir. Bu araştırmada havacılıkta özellikle MRO servisini desteklemek için lojistik uygulamalarına ve bu süreçlerdeki iyileştirmelerden elde edilecek kazanımlara odaklanılmıştır. Havacılık endüstrisinde hizmet sektörünün temel unsuru olarak MRO kavramı ve MRO hizmetlerinin genel süreçleri tanımlanacaktır. Lojistiğin MRO üzerindeki etkisi incelenecek ve ilgili birimler üzerindeki modellemeleri yapılacak ve bu kapsamda hangi alanlarda ne kadar zaman ve iş kayıpları oluştuğunu tespit etmek için Pareto ve Kök-Neden analizleri ile saptanacaktır. Analiz sonuçlarına göre önemli alanlara odaklanılarak, gerekli iyileştirme çalışmaları daha efektif bir şekilde uygulanacaktır
Havacılık Bakım Onarım Merkezinde Lojistik Süreçlerinin Geliştirilmesi; THY Teknik A.Ş. Örneği
Keywords: Business Administration; İşletme